Manajemen Ketersediaan dan Penggunaan Air pada Rumah Tangga Berbasis IoT - Mochamad Susantok; Tama Ramadhan (Jurnal Elektro dan Mesin Terapan, 2021)
Water one of important resource which needs to be managed wisely, especially at home usage. Water management at home is about control water availability on a water tank and monitoring how many liters of daily usage. To improve that issue, in this paper we propose an integrated system that allows managing water in two functions, first to maintain the water level in the water tank is about 15%-85% from water tank capacity. Second, users can monitor water usage real-time in daily for efficiency purposes. This system consists of sensors that connect through the internet using NodeMCU ESP8266 as a microcontroller to collect data of sensors and send them to the Blynk cloud server as an IoT platform. Another side, the Blynk app installed on the user smartphone can read data sensors that storage in the Blynk server, as monitoring to analyze water usage and water level in the water tank. The result of this system is working properly with a percentage error 1,96% - 3.84% for minimum and maximum threshold control water level in the water tank. The accuracy of water usage is about 98,28% or 1.72% error rate. This system proved can help the user easily with their smartphone to manage water availability automatically and to analyze water usage for efficiency purposes.